Lignin-Based Electrospun Carbon Nanofibers - Kumar, Manish; Hietala, Maiju; Oksman, Kristiina (Frontiers in Materials, 2019)
The article summarizes the scientific progress that has occurred in the past several years in regard to the preparation of carbon nanofibers from lignin as a low-cost environmentally-friendly raw material using electrospinning. It presents an overview of using lignin, electrospinning, and carbonization to convert lignin to carbon nanofibers. Lignin is a renewable source for carbon material, and it is very abundant in nature. It is mostly produced as a byproduct from the paper industry and biomass fractionation. Despite its extensive availability and beneficial properties, only a few studies have reported on its use in electronic applications. Lignin-based carbon nanofibers have a high surface area, high porosity, and good electrical conductivity; thus, it is proposed that they are suitable for future energy storage applications.